President's Message - Socha, Linda (Operating Room Nurses Association of Canada Journal, 2007)
This evening, as I sit here writing my first solo president’s message, I am reflecting on what a busy year 2007 has already been. The 20th National ORNAC Conference, held in Victoria in April, was amazingly successful in many ways. The event had fantastic delegate turnout, including the largest international delegate turnout in ORNAC’s history, offered a comprehensive array of plenary sessions, and featured an impressive industry representation.